C-Type Ops Transformation - Ahmad Lazwardi; Iin Ariyanti; Soraya Djamilah (CAUCHY: Jurnal Matematika Murni dan Aplikasi, 2022)
Many indexes are involved on ordinary power series calculation. One of the most valuable discovery on previous research is Ops Transformation which able to simplify notations of ordinary power series to avoid some more complicated manipulations. The aim of this research is to generalize the concept of Ops Transformation to gain more benefit and wider applications. The main result of this research is a new formula of generalization of Ops Transformation which called C-Type Ops Transformation. Such transformation is able to solve some differential equations which involving Taylor series